2022
DOI: 10.31234/osf.io/9s43u
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An itsy bitsy audience: Live performance facilitates infants’ attention and heart rate synchronization

Abstract: Among our most powerful experiences are those we share with others. Researchers have increasingly sought to investigate responses to socially potent stimuli, such as music, in contexts that are more naturalistic than a traditional psychology lab. Here, we investigated behavioral and physiological responses to either a live concert or a perceptually-matched recorded playback on a naïve audience: infants. Two audiences of 6- to 14-month-old infants (N = ~30 each, total N = 61) watched a musical performance live … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…In a live music concert with caregiver-infant dyads as the audience, 6to 18-month-old infants' attention, affect, and movement were modulated by the song style, their caregivers' attention and level of engagement, and the infants' own musical experience (Kragness et al, 2023). In another concert of ID performances, infant audience members' attention and heart rates synchronized more with those of other infants during live compared to prerecorded shows (Kragness, Eitel, et al, 2022). These studies suggest that live music experience, whether between a dyad or in a larger social group, enhances coordination of arousal and attention.…”
Section: Effects Of Live Musical Interactions On Engagement and Movementmentioning
confidence: 97%
See 1 more Smart Citation
“…In a live music concert with caregiver-infant dyads as the audience, 6to 18-month-old infants' attention, affect, and movement were modulated by the song style, their caregivers' attention and level of engagement, and the infants' own musical experience (Kragness et al, 2023). In another concert of ID performances, infant audience members' attention and heart rates synchronized more with those of other infants during live compared to prerecorded shows (Kragness, Eitel, et al, 2022). These studies suggest that live music experience, whether between a dyad or in a larger social group, enhances coordination of arousal and attention.…”
Section: Effects Of Live Musical Interactions On Engagement and Movementmentioning
confidence: 97%
“…Piazza and colleagues specifically showed that when children successfully learned new words together, they also showed similar brain activities. A similar approach could therefore be utilized to assess how large groups of children process music collectively during live performances (Kragness, Eitel, et al, 2022;Kragness et al, 2023). Studying additional multiperson settings, such as with siblings or in a daycare context, might also deepen our understanding of how infants process music in a social context.…”
Section: Multi-person Brain Measurementsmentioning
confidence: 99%
“…In a live music concert involving singing and musical instruments with caregiver-infant dyads as the audience, 6-to 18-month-old infants' attention, affect, and movement were modulated by the song style, their caregivers' attention and level of engagement, and the infants' own musical experience (Kragness et al, 2023). In another concert of ID performances, infant audience members' attention and heart rates synchronized more with those of other infants during live compared to prerecorded shows (Kragness, Eitel, et al, 2022). These studies suggest that live music experience, whether between a dyad or in a larger social group, enhances coordination of arousal and attention.…”
Section: Effects Of Musical Interactions On Engagement and Movementmentioning
confidence: 99%
“…A growing body of research has started examining this issue from a bio-behavioral perspective with a focus on how infants perceive and respond to music made for them (Cirelli, Jurewicz, et al, 2020b;Kragness, Eitel, et al, 2022;Lense, Shultz, et al, 2022;Markova et al, 2020;T. Nguyen et al, 2023).…”
Section: Future Perspectives: Decoding Early Musical Interactionsmentioning
confidence: 99%
See 1 more Smart Citation